Curriculum management practices at MAN 1 Bone: A case study of a madrasah plus skills institution - Juliani D, Devi Riska; Usman, Syahruddin; Syamsudduha, St.; Halimah, Andi; Idris, Ridwan (Abjadia : International Journal of Education, 2025)
This study aims to analyze the management of MAN 1 Bone's curriculum as a Madrasah Plus Skills program. This research employs a qualitative approach, utilizing a phenomenological method, and incorporates data collection techniques that include interviews, observation, and documentation. The key informants in this study included the head of madrasah, deputy head of madrasah, vocational teachers, and vocational students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of this study show that: 1) Curriculum planning includes preparing program objectives, flexibility in teaching materials, integrating theory and practice in learning strategies, and designing holistic evaluations. 2) Curriculum Organization includes a clear division of tasks, integration of skills material in local content and special classes, and optimization of resources to support learning strategies. 3) Curriculum Implementation includes Fashion styling is taught in intracurricular and special classes with teaching modules, while welding is only through special afternoon classes with lesson plans with learning strategies, and evaluations covering student theory and practice. 4) Evaluation of the Curriculum shows tangible benefits in the mastery of vocational skills, despite challenges such as time constraints, low interest, and a lack of instructors. This study contributes practical insights for developing vocational-oriented curriculum management in Islamic educational institutions, especially madrasahs.